Review on Lodhra (Symplocos Recemosa Roxb) in the Management of Raktapitta (Bleeding Disorder). - Santra, Monika; Meenakshi, Vaddi; Ghosh, Sukumar (International Research Journal of Ayurveda & Yoga, 2022)
Lodhra (Symplocos recemosa Roxb) is an important medicinal plant mentioned in Ayurvedic classics and Nighantus for the treatment of Raktapitta (bleeding disorder), Pradara (Leucorrhoea), Atisara (diarrhoea), Pravahika (Dysentery), Netraroga (conjunctivitis), and sotha (inflammation). Stem bark is the useful part of this drug. Raktapitta (bleeding disorder) is a Pittaprokapak and Raktaproodushak vyadhi. Pittadushita Rakta comes out from major and minor outlets of the body such as mukha (mouth), nasa (nose), chakshu (eye), karna (ear), mootra marga (urinary tract), payu (anus), Yonimarga (vaginal area) etc. Excess intake of pitta prokopa ahara, vihara, and manasik hetu leading to development of this clinical condition. Rational use of Sodhana, samana,and nidan paribarjan are the line of management of this deadly disease.